2008
DOI: 10.1126/science.1166340
|View full text |Cite
|
Sign up to set email alerts
|

Germ Cell-Intrinsic and -Extrinsic Factors Govern Meiotic Initiation in Mouse Embryos

Abstract: Retinoic acid (RA) is an essential extrinsic inducer of meiotic initiation in mammalian germ cells. However, RA acts too widely in mammalian development to account, by itself, for the cell-type and temporal specificity of meiotic initiation. We considered parallels to yeast, in which extrinsic and intrinsic factors combine to restrict meiotic initiation. We demonstrate that, in mouse embryos, extrinsic and intrinsic factors together regulate meiotic initiation. The mouse RNA-binding protein DAZL, which is expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
211
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(224 citation statements)
references
References 24 publications
9
211
2
2
Order By: Relevance
“…Recently, it was shown that by E14.5, murine germ cell numbers are significantly decreased in both male and female Dazl -/ -embryos, concomitant with reduced marker expression of Vasa and SCP3 [18]. Of note, 2 other studies conducted using a murine model reported that either loss of PGCs occurred at E14.5 only in Dazl -/ -males [20] or was initiated at a considerably later stage (E15.5 to E17.5) of development [8]. Irrespective of the timing, Haston et al showed that in Dazl -/ -males, imprint erasure was delayed or incomplete, and while PGCs derived from female mutant animals did enter meiosis, there appeared to be a block in meiotic progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that by E14.5, murine germ cell numbers are significantly decreased in both male and female Dazl -/ -embryos, concomitant with reduced marker expression of Vasa and SCP3 [18]. Of note, 2 other studies conducted using a murine model reported that either loss of PGCs occurred at E14.5 only in Dazl -/ -males [20] or was initiated at a considerably later stage (E15.5 to E17.5) of development [8]. Irrespective of the timing, Haston et al showed that in Dazl -/ -males, imprint erasure was delayed or incomplete, and while PGCs derived from female mutant animals did enter meiosis, there appeared to be a block in meiotic progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of DAZL in 12.5-dpc PGCs (a time point that coincides with the mitotic to meiotic transition) is 28-fold higher than in 10.5-dpc (mitotic) PGCs in mice [19], suggesting that it may also play a role during meiosis. It has been reported that DAZL is necessary for the expression of Stra8 and meiotic initiation in embryonic ovaries, indicating that it is an intrinsic meiotic competence factor having an obligatory function upstream of meiotic initiation [20]. Using Dazl-null mice, Haston et al demonstrated that Dazl is required for the differentiation of murine PGCs, a process involving the transition from mitosis to meiosis, as well as imprint erasure through epigenetic programs [18].…”
Section: Discussionmentioning
confidence: 99%
“…What biological activity might RHOX10 have in the cytoplasm of gonocytes? Given RHOX10's male-specific expression pattern in fetal germ cells (Daggag et al 2008), we suggest that cytoplasmic RHOX10 might participate in preventing gonocytes from entering meiosis, as only male fetal germ cells, not female fetal germ cells, avoid initiating meiosis until puberty (Lin et al 2008). Cytoplasmic RHOX10 might also participate in the male-specific mitotic arrest that occurs as male germ cells undergo differentiation into gonocytes in the fetal testis (Culty 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recent results suggest that DAZL may be a 'meiosis competence' factor (Lin et al 2008). In the Dazl KO, on a C57BL/6 background, RA is unable to trigger upregulation of Stra8, increased Sycp3 transcription and translation are not observed, and the double strand breaks characteristic of meiosis do not form.…”
Section: What Makes a 'Meiosis-competent' Germ Cell?mentioning
confidence: 99%